Exit and Paradise Creek Braid Plain Kilometers, 2012 - Curran, Janet H. (ORCID: 000-0002-3899-6275); Williams, Haley B. (USGS Science Data Catalog, 2017)
This dataset consists of points designating braid plain kilometers, or distance along the braid plain centerline, for the 2012 active braid plain of Exit Creek and of Paradise Creek from its mouth to 0.5 km along its unnamed western fork, respectively.